Siemens: a multinational's strategy to investment in the Central-East European transformation countries - Birgit Sander (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
The Central East European economies are competing for international investment capital, especially for FDI in order to support transformation. The paper explores how the Siemens AG, one of the world's largest MNCs, allocates investments towards and within Central East Europe and how they fit into its overall corporate strategy. They display strategic asset features, are targeted to cheap resources, meant to serve either national or international markets and rely on different degrees of functional integration.
Keywords: D21; F21; F23; D23; L22; 330; Multinationales Unternehmen; Direktinvestition; Wettbewerbsstrategie; Elektroindustrie; Deutschland; Osteuropa